2013
DOI: 10.1186/1465-9921-14-46
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exacerbations of cystic fibrosis on muscle strength

Abstract: BackgroundAdult patients with cystic fibrosis have peripheral muscle weakness, which is related to exercise intolerance and poor prognosis. The influence of acute exacerbations on muscle strength has been poorly studied. This study aimed to investigate whether quadriceps force (QF), as assessed with an involuntary technique, changes during intravenous antibiotics therapy (IVAT) for an exacerbation.MethodsQF was measured in 20 patients using twitch stimulation of the femoral nerve at the day of hospitalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
1
44
0
1
Order By: Relevance
“…Many factors may potentially contribute to reduced muscle CSA in CF, such as inflammation [18], medication [19], repeated exacerbations [20], altered nutritional status [7] or physical inactivity [6]. In our study, we only found a slight tendency for reduced qCSA in CF (14%), which is consistent with previous findings in more severe patients (14%, P = 0.05) [18].…”
Section: Discussionsupporting
confidence: 93%
“…Many factors may potentially contribute to reduced muscle CSA in CF, such as inflammation [18], medication [19], repeated exacerbations [20], altered nutritional status [7] or physical inactivity [6]. In our study, we only found a slight tendency for reduced qCSA in CF (14%), which is consistent with previous findings in more severe patients (14%, P = 0.05) [18].…”
Section: Discussionsupporting
confidence: 93%
“…a Within CF able to discriminate between exacerbation and stable patients. a [2,20] Evidence of significant correlation with exercise capacity a , strength a , bone mineral density a , kyphosis a , and lung function a [2,[20][21][22] Evidence of responsiveness to IVAB a . [18,20,23] ActiGraph Evidence of responsiveness to IVAB a .…”
Section: Reliabilitymentioning
confidence: 99%
“…a [2,20] Evidence of significant correlation with exercise capacity a , strength a , bone mineral density a , kyphosis a , and lung function a [2,[20][21][22] Evidence of responsiveness to IVAB a . [18,20,23] ActiGraph Evidence of responsiveness to IVAB a . [24,25] Evidence of correlation with the HAES and the 7 day PAR questionnaires and the Bratteby activity diary a, b,c [24,25] Within CF able to discriminate between gender a, b, c and disease severity b, c [15,24] Evidence of significant correlation with exercise capacity a, b, c [3] Evidence of responsiveness to a physical conditioning program a, b, c [5] RT3 Evidence of significant correlation with step rate/count and respiratory symptoms diary and lung function a, b [29] Evidence of responsiveness to IVAB a, b [29] a Adults.…”
Section: Reliabilitymentioning
confidence: 99%
“…Similarly to the recruitment process, if a patient was not well enough to engage in their regular HPA, their data collection was postponed until a visit at which their typical HPA patterns had resumed, to control for potential losses in muscle force, and the documented reductions in HPA during exacerbation [16]. As a result, the number of data points varied among patients for the study period.…”
Section: Data Collectionmentioning
confidence: 99%